Nilai-Nilai Yang Terkandung Pada Tari Kombuik Di Desa Gunung Sahilan Kecamatan Gunung Sahilan Kampar Kiri Kabupaten Kampar - Uswatun Hasanah; Yahyar Erawati (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to determine the values contained in the Kombuik Dance in Gunung Sahilan Village, Gunung Sahilan Kampar Kiri District, Kampar Regency. The results of this research conclude that the religious values contained in the Kombuik dance are the religious values contained in this dance, namely in this dance, in the middle of the dance, the dancers form a circle and recite prayers and prayers which are intended as a form of gratitude to Allah SWT has provided sustenance and the gift of health so that it can continue. Traditional values, this dance continues to exist to this day because it is maintained by Gunung Sahilan Village, a form of how the local community maintains this art is that this dance continues to be taught to the next generation, so that we can continue to enjoy this art at every holiday event. you gun